(untitled) (Vietnam Journal of Community Medicine, 2023)
Objective: To describe the current situation of pre-marital sex of students in Dai Nam University and some related factors. Method: Cross-sectional descriptive study conducted on 336 health students Dai Nam University in 2022. Results: The percentage of students who had a lover was 46.7%, and 16.1% had sex before marriage. Male students have more sex before marriage (18.9%) than female students (14.5%). Regarding the issue of safe sex, among the research subjects who had ever had sex, 78.3% of subjects used contraception, and 21.7% of subjects did not use contraceptives. Important factors related to sexual behavior before marriage found in this study include: place of residence; sharing with parents about issues related to love, sex, and reproductive health; love relationship status; Students’ views on the issue of pre-marital sex; watching movies/photos with pornographic content; use alcohol and stimulants. Conclusion: The rate of pre-marital sex among health students at Dai Nam University is high. Factors related to pre-marital sexual behavior include place of residence, relationship status, information sharing with parents, students’ opinions, and other health risk behaviors.